Delivering Remote Measurement-Based Care in Community Addiction Treatment: Engagement and Usability Over a 6-Month Clinical Pilot - Hallgren, Kevin A.; Cohn, Eliza B.; Ries, Richard K.; Atkins, David C. (Frontiers in Psychiatry, 2022)
Objective: Measurement-based care (MBC) is an evidence-based practice in which patients routinely complete standardized measures throughout treatment to monitor clinical progress and inform clinical decision-making. Despite its potential benefits, MBC is rarely used in community-based substance use disorder (SUD) treatment. In this pilot study, we evaluated the feasibility of incorporating digital and remotely delivered MBC system into SUD treatment within a community setting by characterizing patients’ and clinicians’ engagement with and usability ratings toward the MBC system that was piloted. Methods: 30 patients and 8 clinicians participated in this clinical pilot. Patients were automatically sent links to complete a 22-item questionnaire, called the weekly check-in, via text message or email weekly for 24 weeks. Results of the weekly check-in were summarized on a clinician-facing web-based dashboard. Engagement was characterized by calculating the mean number of weekly check-ins completed by patients and the mean number times clinicians logged into the MBC system. Ratings of the MBC system’s usability and clinical utility were provided by patients and clinicians at multiple time points. Results: Patients completed a mean of 20.60 weekly check-ins (i.e., 85.8% of the 24 expected per patient). All but one participating clinician with a patient enrolled in the study logged into the clinician-facing dashboard at least once, with an average of 12.20 logins per clinician. Patient and clinician ratings of usability and clinical utility were favorable: most patients agreed with statements that the weekly check-in was easy to navigate and aided self-reflection. All clinicians who completed usability questionnaires agreed with statements indicating that the dashboard was easy to navigate and provided information that was meaningful for SUD treatment. Conclusions: A digital and remotely delivered MBC system can yield high rates of patient and clinician engagement and high ratings of usability and clinical utility when added into SUD treatment as usual. The success of this clinical pilot may be attributable, in part, to the user-centered design processes that were used to develop and refine the MBC system that was piloted. Future efforts may focus on strategies to test and sustainably implement MBC systems in community SUD treatment settings.